DEMOCRATIC MODEL OF COMMUNICATION IN THE SYSTEM OF PUBLIC ADMINISTRATION OF UKRAINE: ESSENCE AND MAIN ELEMENTS - Prysyazhnyuk , Petro (Theory and Practice of Public Administration, 2019)
This article democratic model of communication in the system of public administration of Ukraine, its essence, and also its basic elements are analyzed. The author studied the theoretical and practical aspects of the relevance of the creation of a democratic model of communication as an part of the government system. The humanization of communication between citizens and the state on the basis of human-centricity requires the creation of a theoretical model. Such a communication process should be considered at an abstract level and then embody the practical implementation of the idea of ​​strengthening democracy in Ukraine, in particular by democratizing communication between citizens and the state. For this purpose it is necessary to create such a model that will take maximum account of all circumstances of communication of citizens with the state. In the paper it is noted that communication models were created by scientists of different specialties. These are sociologists, psychologists, linguists, mathematicians, political scientists, government officials, communications professionals, etc. It is especially noted that models of mass communication were most often created. The most famous are the communication models of such authors: Lasswell H. D., Shannon C.E. and Weaver W., Westley and MacLean’s, Braddock R., De Fleur, Dance F., Schramm W., Barnnlund D.C. Maletzke G. Carey James W. The article describes the democratic model of communication between citizens and state government or local government in Ukraine. The model has the form of an infinity symbol. The author focuses on internal and external factors influencing the communication process.The article describes perspective directions of research of modeling of communication between citizens and state bodies and local self-government. This is a (creating other communication models) search for other communication models between citizens and state government or local government in Ukraine and more.